Mendesain Kewenangan Kekuasaan Kehakiman Setelah Perubahan UUD 1945 - Subiyanto, Achmad Edi (Jurnal Konstitusi, 2012)
After the Amendment of the 1945 Constitution of The Republic of Indonesia, The Judicial Power has become the most fundamentally power and also as a part of the axis of power which its function is to enforce justice. According to the Amendment  of the 1945 Constitution of The Republic of Indonesia, the judicial power in the structure of state power,  is still placed at the power that is free from intervention   or influence from other power in exercising its authority. In the structure of state power, after the Amendment of the 1945 Constitution of The Republic of Indonesia, the judicial power shall be implemented by a Supreme Court and judicial bodies underneath it in the form of public courts, religious affairs courts, military tribunals, and state administrative courts, and by a Constitutional Court. The Amendment of the 1945 Constitution of The Republic of Indonesia, also spawned a new institution, beside Constitutional Court which its function is relating to judicial power, namely an independent Judicial Commission which shall possess the authority to propose candidates for appointment as justices of the Supreme Court and shall possess further authority to maintain and ensure the honour, dignity and behaviour of judges.